Valuation of Railways, with Especial Reference to the Physical Valuation in Minnesota - Dunn, Samuel O. (Journal of Political Economy, 1909)
During recent years there has been much discussion of valuation of the physical properties of railways as a basis for public regulation of their rates. The subject has been moved a good way from the field of academic theory to that of applied theory by the exhaustive physical valuation of the railways of Minnesota, which recently was completed by the railroad commission of that state. There were "physical valuations" before that in Minnesota, notably that in Texas in I894; that in Michigan in i900; and that in Wisconsin in 1903. But the valuation in Texas recently was admitted by the engineer who made it to be entirely out of date; and it never was entitled to much respect. None of these valuations was so exhaustive as that in Minnesota; and those in Michigan and Wisconsin were made as bases for taxation, not rate-regulation. The railroad commission of Washington finished a physical valuation of the railways in that state for purposes of state-regulation at about the same time that the Minnesota commission completed its work. But the valuation in Washington relates to only a few roads, built and operated under somewhat unusual conditions, while the Minnesota valuation relates to nineteen carrying and six switching, or terminal roads, having an aggregate line-mileage of 7,596 miles and an aggregate trackmileage of 10,437 miles, built and operated under physical and commercial conditions similar to those in a large part of the